The effect of mastication muscular tone on facial size in patients with Down syndrome - Margaretha Suharsini; Josef Glinka SVD; Soekotjo Djokosalamoen (Dental Journal (Majalah Kedokteran Gigi), 2006)
Muscular hypotonia is one of the clinical signs in patients with Down syndrome. As a characteristic of patients with Down syndrome, hypotonia is clearly evident in face expression and oral dysfunction. Dentocraniofacial growth abnormalities in patients with Down syndrome may be influenced by genetic and environmental factors. Stomatognathic system musculature as an environmental factor (factor outside the bone) can affect dentocraniofacial growth by orofacial muscles activities when chewing, swallowing, breathing, and speaking. Oral dysfunctions commonly seen in patients with Down syndrome are open mouth, protruding tongue posture, difficulties when chewing, swallowing, and speaking, drooling, and mouth breathing. The purpose of this study was to observe how the mastication muscular tone affecting the facial size of Down syndrome patient. Twenty five of 14–18 years old children with Down syndrome were diagnosed by clinical characteristic and cytogenetic examination. Mastication muscular tone was described by masseter and temporalis muscle synergy and oral function, whereas the facial size consisted of facial size of lateral, anteroposterior and vertical growth. The result of regression test revealed that the degree of mastication muscular tone has a significant effect on facial size of the anteroposterior growth and facial size of vertical growth, but did not significantly influence the facial size of lateral growth.